2003
DOI: 10.1056/nejme030018
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin for Venous Thromboembolism — Walking the Dosing Tightrope

Abstract: The new england journal of medicine n engl j med 348;15 www.nejm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…Interestingly, our patients were on treatment for over 3 months, showing that this hypercoagulability is not restricted to initial treatment states. The results are also in accordance with the finding of increased in vivo prothrombin turnover at low-intensity VKA treatment [7], as well as with the observation that low INR values have been shown to be inadequate for the prevention of myocardial infarction [8] whereas they may or may not have an effect in venous thrombosis [9]. This might suggest that the role of TM differs with the underlying pathology.…”
supporting
confidence: 89%
“…Interestingly, our patients were on treatment for over 3 months, showing that this hypercoagulability is not restricted to initial treatment states. The results are also in accordance with the finding of increased in vivo prothrombin turnover at low-intensity VKA treatment [7], as well as with the observation that low INR values have been shown to be inadequate for the prevention of myocardial infarction [8] whereas they may or may not have an effect in venous thrombosis [9]. This might suggest that the role of TM differs with the underlying pathology.…”
supporting
confidence: 89%
“…Assuming rhythm control is the active intervention: RRI = Relative Risk Increase, and a negative NNT value amounts to a 'Number Needed to Harm' (NNH); NNT/year values exceeding 1000 (whether positive or negative) imply negligible effects; Secondary composite endpoint = death, disabling stroke, disabling anoxic encephalopathy, major bleeding, or cardiac arrest; Primary composite endpoint = cardiovascular death, heart failure, thromboembolism, bleeding, pacemaker implantation or severe anti-arrhythmic drug adverse effect. a better benefit/safety profile than with previously advocated higher intensity treatment (6,7). Similarly, better evidence is needed to determine the optimal international normalization ratio for patients who receive long-term warfarin for atrial fibrillation.…”
mentioning
confidence: 92%
“…All PA are of some danger in inducing severe hemorrhages (2,13). Fibrin is not only found in the pathologic thrombus, but also circulates as soluble fibrin polymers in the blood and possesses physiologic functions in the prevention of blood loss or the prevention of bleeding in vital organ areas (14,15). If clinical plasmatic thrombolysis is required, it is suggested that the physiologic activators urokinase or t-PA might be preferred.…”
Section: Discussionmentioning
confidence: 99%